Double taxation treaties and resource revenue mobilization in developing countries: A neural network approach - Harouna Kinda; Abrams Mbu Enow Tagem (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Double taxation treaties, by assigning taxing rights to rival countries and thereby eradicating double taxation, aim to facilitate cross-border trade and investment. The eradication of double taxation is achieved through reductions in withholding tax rates on passive income in source countries, resulting in revenue losses. Multinational corporations structure their investments to benefit from treaty-reduced withholding tax rates, exacerbating the revenue losses. These phenomena are especially important in resource-rich countries, where international expertise and multinational corporations dominate the scene, posing challenges to revenue mobilization. This paper investigates the effects of double taxation treaties on resource revenue mobilization in 83 resource-rich countries from 2000 to 2019 by applying standard panel fixed effects and methods-of-moments approaches. We calculate countries' centrality indices by year on the basis of their importance in the tax treaty network and show that centrality indices have a negative relationship with resource revenue mobilization-findings that are robust to alternative centrality indices and government revenue aggregates. We use the betweenness centrality index to identify countries characterized as intermediate jurisdictions (countries with a betweenness centrality indexabove themedian of countries inthe network for eachyear independently), arguing that multinational companies structure theirinvestments to benefit from the low withholding tax rates in these countries. Applying the entropy balancing method, we find evidence of a negative effect of signing tax treaties with country-classified investment hubs on resource revenue mobilization.
Keywords: F21; F23; H26; Q32; 330; centrality indices; double taxation treaties; entropy balancing; resource revenue mobilization; withholding taxes